Distribution of minerals in cow's milk - AKAI, Tatuo; SATOH, Akira; IMAMURA, Tsuneaki (Nihon Eiyō, Shokuryō Gakkai shi, 1984)
The distribution of ash and twelve kinds of elements in cow's milk were examined. For this purpose, individual raw milks were collected from eight healthy cows and fractionated by the following different methods. The individual whole milk (a) was separated into skim milk (b) and cream (c) by centrifugation, and skim milk fraction was further separated into casein (d) and whey (e) by three different ways, i. e. , ultracentrifugation, acidification, and addition of rennin. These three types of casein were designated as ultracentrifugal, acid- and rennin-casein. The cream fraction (c) was well washed with water and the residue was designated as the washed cream (f). For each fraction, the amounts of ash and the twelve elements, i. e. , Na, K, Ca, Mg, Zn, Fe, Cu, Mo, Mn, Co, Al and P were determined, of which the eleven metallic elements were determined with Hitachi Polarized Zeeman Atomic Absorption Spectrophotometer, and P by a Molybdenum-Blue method. The ratios of b/a, c/a, d/b, e/b and f/c for the contents of ash and the twelve elements were calculated and illustrated. The figures of b/a and c/a indicated that Mo, Fe, Co, Cu, Mn and Al were contained at higher concentra-tion in the cream fraction than in the skim milk fraction. Four of above elements, i. e. , Mo, Fe, Co and Cu remarkably remained in the washed cream fraction. They are considered to bind tightly to some surface substances of fat globule. The figure of e/b indicated a fall in the contents of several elements (Ca, Fe, Cu, Zn, Mo and P) in the whey fraction, which suggests a presence of bound type of these elements in casein micelle. In fact, the ultracentrifugal casein fraction contained the six elements at remarkably higher concentration. The pattern of mineral composition of the rennin-casein fraction resembled to that of the ultracentrifugal casein fraction, but not to that of the acid-casein. fraction. Almost all the amount of Zn in the whole milk migrated to the ultracentrifugal casein frac-tion, but the amount of Zn found in the acid-casein fraction was a half of that of the whole milk. The contents of Ca, Mg, Al and P decreased in the acid-casein fraction. These findings suggest that dissociable type of binding contributes to the occurrence of these elements around the casein micelle.